Context-dependent role of selective attention for change detection in multi-speaker scenes - Starzynski, Christian; Gutschalk, Alexander (Human brain mapping, 2018)
Disappearance of a voice or other sound source may often go unnoticed when the auditory scene is crowded. We explored the role of selective attention for this change deafness with magnetoencephalography in multi-speaker scenes. Each scene was presented two times in direct succession, and one target speaker was frequently omitted in Scene 2. When listeners were previously cued to the target speaker, activity in auditory cortex time locked to the target speaker's sound envelope was selectively enhanced in Scene 1, as was determined by a cross-correlation analysis. Moreover, the response was stronger for hit trials than for miss trials, confirming that selective attention played a role for subsequent change detection. If selective attention to the streams where the change occurred was generally required for successful change detection, neural enhancement of this stream would also be expected without cue in hit compared to miss trials. However, when listeners were not previously cued to the target, no enhanced activity for the target speaker was observed for hit trials, and there was no significant difference between hit and miss trials. These results, first, confirm a role for attention in change detection for situations where the target source is known. Second, they suggest that the omission of a speaker, or more generally an auditory stream, can alternatively be detected without selective attentional enhancement of the target stream. Several models and strategies could be envisaged for change detection in this case, including global comparison of the subsequent scenes.